Advanced surgical technique for invasive fungal sinusitis: endoscopic orbit-sinus combined approach. Issue 5 (3rd September 2017) - Nishimura, Kunihiro; Takahashi, Yasuhiro; Yamagishi, Yuka; Banno, Shinya; Uchida, Yasue; Tanigawa, Tohru; Naito, Munekazu; Kakizaki, Hirohiko; Ueda, Hiromi; Ogawa, Tetsuya
Abstract: Background: Invasive fungal sinusitis is usually associated with poor prognosis, but no clear guidelines have been established for surgical treatment. Here, we report the development and application of the endoscopic orbit-sinus combined approach (EOSCA), a novel surgical technique to approach the nasal cavity and orbit concurrently, in patients with invasive fungal sinusitis with orbital infiltration. Material and methods: Two patients with invasive fungal sinusitis infiltrating the orbit underwent EOSCA. Transnasal endoscopy was performed for maximum debulking of tissues infiltrated by fungi in the nasal cavity and orbit, before making an incision into the palpebral conjunctiva. An endoscope was then inserted into the orbit through the incision in the palpebral conjunctiva to remove adipose tissue and muscles that had been infiltrated by fungi from the orbital regions where the transnasal approach was difficult or impossible. Another surgeon assisted the procedure by operating an endoscope concurrently via the nasal cavity (four-hands technique). Results: We were able to remove lesions safely and with precision, preserving visual acuity and a functional eyeball in both cases. Currently, the patients are alive, with no postoperative complications, recurrence, or disfigurement. Conclusions: This novel method shows promise as a safe and reliable surgical procedure for patients with invasive fungal sinusitis infiltrating into the orbit, with no postoperative complications, recurrence, or disfigurement.